Managing a medieval frontier: government policy towards the Irish marches and the lands beyond them, c.1200-c.1318 - Keane, Eoghan (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2021)
This thesis explores methods employed by the Dublin administration during the long thirteenth century in its efforts to manage the colonial frontiers and to minimise their impingement on government activities and finances. Some of the measures examined were systematic in nature, while others were implemented on a more ad hoc basis in response to local circumstances. Collaboration between the king and his Irish representatives played an important role in policy formation, as did consultation and negotiation with those directly involved on the frontiers. Throughout the thesis, efforts are made to establish the location, simultaneously both geographical and hierarchical, of policy formation, as well as the actual operation of the measures examined. Government policy towards the frontiers was situational, often short-lived, and closely tied up with magnate patronage. The Dublin government s considerable freedom of independent action within Ireland, and its influence over royal thinking and policy towards the Irish frontier, are clear. So, too, is the unreality of efforts to centralise power while simultaneously decentralising the responsibilities and expenses of frontier defence. The study affords a window onto the operation of government in Ireland, as well as the relations between the king, his Irish government, and the frontiers two layers of core and periphery.
APPROVED
Keywords: Medieval Ireland; Frontier Studies; Medieval Government; Thirteenth Century; History; Marches